Features of Myocardial Revascularization in Multifocal Atherosclerosis with Involvement of Coronary Arteries and Lower Limb Arteries - Gabriyelyan, Artur V.; Cheveliuk, Oleksandr V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The presence of a combination of coronary artery disease (CAD) and peripheral artery disease (PAD) is associated with nearly double all-cause mortality rate, up to 4.6% per year, compared to the mortality rate for each of the conditions. Performing the first-stage intervention on the arteries of the lower limbs carries a high risk of the coronary blood flow worsening in the form of perioperative myocardial infarction, while isolated coronary artery bypass grafting (CABG) may exacerbate ischemia of the lower limbs. The following questions remain unresolved: What should be the sequence and timing of surgical interventions in the combination of CAD and PAD? Do simultaneous surgical interventions have advantages over staged interventions? What is the optimal graft choice for CABG? What is the optimal technique for myocardial revascularization? The aim. To study the features of myocardial revascularization in patients with multifocal atherosclerosis affecting both coronary arteries and arteries of the lower limbs. Materials and methods. We analyzed the treatment outcomes in 48 patients with combined coronary artery and lower limb artery disease from 2016 to 2023, as well as data from contemporary literature from 2018 to 2023, which covered over 14,000 patients. Surgeries were performed without cardiopulmonary bypass, both simultaneously and in stages. Venous and arterial grafts were used during the interventions. Results. The patients who underwent simultaneous operations demonstrated a higher incidence of wound complications (p < 0.001). The patients who underwent staged procedures experienced more severe limb ischemia requiring intervention (p < 0.001) than those who had simultaneous procedures. No cases of acute cerebrovascular accidents were noted in either group. In both groups, early postoperative periods were marked by rhythm disturbances, specifically paroxysms of atrial fibrillation, which were successfully managed conservatively. There were no hemorrhagic complications associated with prolonged heparinization during simultaneous procedures compared to staged interventions. The patients who underwent either simultaneous or staged myocardial revascularization and vascular reconstruction of the lower limbs rarely experienced complications related to vascular graft thrombosis. Conclusions. The choice of intervention sequence should prioritize CABG as the first step, both in simultaneous and staged interventions. Safe procedures for patients with multifocal atherosclerosis involving coronary and lower limb arteries require a multidisciplinary team. Simultaneous interventions help avoid ischemic complications associated with delaying the next stage of revascularization of other affected vascular territories. Delaying the revascularization of lower limb arteries in staged interventions may lead to the worsening of existing limb ischemia.